Numerical Analysis of Bifurcation Problems of Nonlinear Equations (Journal of Computational Mathematics, 1986)
The paper presents some essential results of branch solutions of nonlinear problems and their numerical approximation. The general theory is applied to the bifurcation problems of the Navier-Stokes equations.